Potential of plant growth promoting bacterial consortium for improving the growth and yield of wheat under saline conditions - Khan, Muhammad Yahya; Nadeem, Sajid Mahmood; Sohaib, Muhammad; Waqas, Muhammad Rashid; Alotaibi, Fahad; Ali, Liaqat; Zahir, Zahir Ahmad; Al-Barakah, Fahad N. I. (Frontiers in Microbiology, 2022)
Owing to inconsistent results of single bacterial strain, co-inoculation of more than one strain under salinity stress could be more effective strategy to induce salt tolerance. Co-inoculation of more than one bacterial strain could be more effective due to presence of several growths promoting traits. Present study was conducted to evaluate the effectiveness of multi-strains bacterial consortium to promote wheat growth under salinity stress. Several plant growth promoting rhizobacteria (PGPR) had been isolated and tested for their ability to grow in increasing concentration of sodium chloride (NaCl). Those rhizobacterial strains having tolerance against salinity were screened to evaluate their ability to promote wheat growth in the presence of salinity by conducting jar trail under axenic conditions. The rhizobacteria with promising results were tested for their compatibility with each other before developing multi-strain inoculum of PGPR. The compatible PGPR strains were characterized, and multi-strain inoculum was then evaluated for promoting wheat growth under axenic conditions at different salinity levels i.e. 2.1 (normal soil), 6, 12 and 18 dS m-1. The most promising combination were further evaluated by conducting pot trial in green house. The results showed that compared to single rhizobacterial strain, better growth promoting effect was observed when rhizobacterial strains were co-inoculated. Multi-strain consortium of PGPR caused significant positive impact on shoot length, root length, shoot fresh weight and root fresh weight of wheat at highest salinity level in jar as well as in pot trial. Results showed that multi-strain consortium of PGPR caused significant positive on biochemical traits of wheat by decreasing electrolyte leakage and increasing chlorophyll contents, relative water contents and K/Na ratio. It can be concluded that multi-strain consortium of PGPR (Ensifer adhaerens strain BK-30, Pseudomonas fluorescens strain SN5, Bacillus megaterium strain SN15) could be more effective to combat the salinity stress owing to presence of variety of growth promoting traits. However, further work is going on to evaluate the efficacy of multi-strain inoculum of PGPR under salt-affected field conditions.